Strategi msdm yang Efektif Dalam Mendorong Pertumbuhan UMKM D'sruput - Herliyani, Ramadhina; Annisa, Siti; Hari Sandi, Santi Pertiwi; Hidayaty, Dwi Epty (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This article discusses effective HRM strategies in driving the growth of D'SRUPUT SMEs. D'SRUPUT SMEs face various challenges, including intense market competition, changing consumer trends, limited resources, and difficulties in building a strong brand. In addressing these challenges, effective HRM strategies become key to improving performance and business growth. In order to optimize HRM strategies, industrial visits to D'SRUPUT SMEs are important to learn successful practices that support SME growth. The data collection method used in this article is structured interviews with D'SRUPUT entrepreneurs in Karawang Regency. The findings from the industrial visits to D'SRUPUT SMEs depict a focus on the food and beverage sector, established in 2019. When starting their business, D'SRUPUT faced challenges competing with more established competitors. The conclusion of this article is that effective HRM strategies are highly relevant in driving the growth of D'SRUPUT SMEs, and the recommendations include implementing these strategies, utilizing appropriate technology, continuous evaluation and improvement, and industrial visits to learn best practices in supporting SME growth. Keywords: HRM Strategies, SME Growth, SME Challenges, Employee Performance Management.